Building Superior Supplier Performance: The Mediating Role of Supplier Satisfaction in the Influence of Client Trust, Contractual Justice, and Payment Reliability - Tokoh Oktaviano, Dewa; Purnomo, Agus; Mulyati, Erna (Dinasti International Journal of Economics, Finance & Accounting, 2026)
The Maintenance, Repair, and Overhaul (MRO) industry in the energy sector is highly dependent on supplier performance. However, PT Torishima Services Indonesia (TSI) faces a supplier performance gap, with actual achievements reaching only 84.75% against a >95% target. This study aims to examine and analyze the influence of Client Trust, Contractual Justice, and Payment Reliability on Supplier Performance, with Supplier Satisfaction acting as a mediating variable. A quantitative explanatory survey method was employed, collecting data from a sample of 128 active suppliers of PT TSI, which was subsequently analyzed using Structural Equation Modeling Partial Least Squares (SEM PLS).Quantitative results demonstrate that client trust (β = 0.091, p < 0.05), contractual justice (β = 0.173, p < 0.05), and payment reliability (β = 0.133, p < 0.05) have a direct, positive, and significant effect on supplier performance. These independent variables also strongly predict supplier satisfaction, with contractual justice emerging as the strongest predictor (β = 0.375, p < 0.05), followed by trust (β = 0.340, p < 0.05) and payment (β = 0.296, p < 0.05). Supplier satisfaction itself exerts a dominant positive influence on performance (β = 0.614, p < 0.05). Furthermore, mediation testing confirms that supplier satisfaction significantly mediates the effects of client trust (β = 0.209, p < 0.05), contractual justice (β = 0.230, p < 0.05), and payment reliability (β = 0.182, p < 0.05) on supplier performance . Theoretically, this study contributes to reinforcing relational governance and supplier relationship management theories by proposing a comprehensive causal model. Practically, management is recommended to implement transparent contractual fairness principles and simplify payment administration procedures to drive sustainable supplier satisfaction and performance. This research offers novelty by simultaneously integrating relational, structural, and financial governance dimensions into a single comprehensive mediation framework within the specific, high risk context of the energy MRO industry, which has not been previously explored.